A Connection Formula of the Hahn-Exton q-Bessel Function - Morita, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We show a connection formula of the Hahn-Exton q-Bessel function around the origin and the infinity. We introduce the q-Borel transformation and the q-Laplace transformation following C. Zhang to obtain the connection formula. We consider the limit p→1⁻ of the connection formula.